Charging and discharging characteristics of absorption thermal energy storage using ionic-liquid-based working fluids. (15th December 2019) - Wu, Wei; Bai, Yu; Huang, Hongyu; Ding, Zhixiong; Deng, Lisheng
Abstract: The absorption thermal energy storage (ATES) systems using H2 O/ionic liquid (IL) mixtures as novel working fluids are explored to avoid the crystallization problem. The property model and cycle model are established and validated against experimental data. The dynamic charging/discharging characteristics and overall cycle performance are compared for four ILs ([DMIM][DMP], [EMIM][Ac], [EMIM][DEP], and [EMIM][EtSO4 ]). Under a typical condition, [DMIM][DMP] yields the highest coefficient of performance (COP) of 0.722 while [EMIM][DEP] yields the lowest COP of 0.603; [DMIM][DMP] shows the highest energy storage density (ESD) of 94.1 kW h/m 3 while [EMIM][DEP] shows the lowest ESD of 77.5 kW h/m 3 ; [EMIM][Ac] needs the longest charging time of 107.5 min, while [EMIM][EtSO4 ] needs the longest discharging time of 207.0 min. Being the best-performing IL in terms of high COP and ESD, [DMIM][DMP] has been further investigated, with charging temperatures of 85–100 °C, cooling water temperatures of 25–35 °C and discharging temperatures of 9–15 °C. The highest COP is 0.761 and the highest ESD is 149.5 kW h/m 3 in the investigated operating conditions. In summary, it is feasible to use H2 O/ILs as crystallization-free working fluids of the ATES systems. This study aims to provide theoretical references and suggestions for the selection of novel working fluids for the ATES systems. Highlights: Absorption thermal energy storage systems using H2 O/ionic liquids are explored. Dynamic charging/discharging characteristics and cycle performance are compared. [DMIM][DMP] has the highest coefficient of performance and energy storage density. [EMIM][Ac] needs the longest charging time but shows the highest discharging rate. The highest energy storage density is 149.5 kW h/m 3 in the investigated conditions.